Certain fractional q-integral formulas for the basic I-function of two variables - UÇAR, FARUK (My University, 2022)
© CSP - Cambridge, UK; I&S - Florida, USA, 2022In the present paper, we derive two theorems involving fractional q-integral operators of Erdélyi-Kober type involving the basic analogue of the I-function of two variables. Corresponding assertions for the Riemann-Liouville and Weyl fractional q-integral transforms are also presented. Several special cases of the main results have also been illustrated.
Keywords: Havacılık ve Uzay Mühendisliği; Matematik; Bilgisayar Bilimleri; Temel Bilimler; Mühendislik ve Teknoloji; Aeronautical and Space Engineering; Mathematics; Computer Science; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; MATEMATİK, UYGULAMALI; MÜHENDİSLİK, HAVACILIK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATHEMATICS; MATHEMATICS, APPLIED; ENGINEERING, AEROSPACE; Modelleme ve Simülasyon; Fizik Bilimleri; Uzay Mühendisliği; Uygulamalı matematik; Modeling and Simulation; Physical Sciences; Aerospace Engineering; Applied Mathematics; Basic analogue of h-function of two variables; Basic analogue of i-function of two variables; Fractional q-integral operators; Q-mellin-barnes double contour integral.